The Influence of E-Customer Relationship Management, E-Service Quality, and Online Value Co Creation on Continuance Use Intention - Rita Fatmala Sari; Syafrizal Syafrizal; Dessy Kurnia Sari (Dinasti Review, 2025)
The rapid development of digital technology has encouraged the banking sector to innovate in digital services. Wondr is an application launched as part of digital transformation. This application offers various advanced features and challenges in retaining users for continuous usage (continuance use intention). This study aims to analyze the influence of E-Customer Relationship Management (E-CRM), E-Service Quality (E-SERVQUAL), and Online Value Co-Creation on the Continuance Use Intention of Wondr users. This research employs a quantitative method with a Structural Equation Modeling - Partial Least Square (SEM-PLS) approach. Data was collected from 382 respondents who are Wondr users using a probability sampling technique. The results indicate that E-CRM and E-SERVQUAL have a positive and significant impact on Continuance Use Intention. Additionally, Online Value Co-Creation, which includes electronic word-of-mouth (e-WOM) and helping behavior, also contributes positively to users' sustainable intention. The implications of this study provide insights for companies to enhance digital banking strategies to maintain user loyalty for Wondr.